Complete genome sequence of Hirschia baltica type strain (IFAM 1418T). Issue 3 (November 2011) - Chertkov, Olga; Brown, Pamela; Kysela, David; Pedro, Miguel; Lucas, Susan; Copeland, Alex; Lapidus, Alla; Glavina Del Rio, Tijana; Tice, Hope; Bruce, David; Goodwin, Lynne; Pitluck, Sam; et al.
Abstract The familyHyphomonadaceae within theAlphaproteobacteria is largely comprised of bacteria isolated from marine environments with striking morphologies and an unusual mode of cell growth. Here, we report the complete genome sequenceHirschia baltica, which is only the second a member of theHyphomonadaceae with a published genome sequence.H. baltica is of special interest because it has a dimorphic life cycle and is a stalked, budding bacterium. The 3, 455, 622 bp long chromosome and 84, 492 bp plasmid with a total of 3, 222 protein-coding and 44 RNA genes were sequenced as part of the DOE Joint Genome Institute Program CSP 2008.